2016
DOI: 10.1186/s12870-016-0732-5
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting chromatin binding of the Arabidopsis UV-B photoreceptor UVR8

Abstract: BackgroundPlants perceive UV-B through the UV RESISTANCE LOCUS 8 (UVR8) photoreceptor and UVR8 activation leads to changes in gene expression such as those associated with UV-B acclimation and stress tolerance. Albeit functionally unrelated, UVR8 shows some homology with RCC1 (Regulator of Chromatin Condensation 1) proteins from non-plant organisms at the sequence level. These proteins act as guanine nucleotide exchange factors for Ran GTPases and bind chromatin via histones. Subsequent to the revelation of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 53 publications
0
24
0
Order By: Relevance
“…However, it should be noted that chromatin association of UVR8 has recently been challenged (39). Independent of this controversy, the GFP-UVR8…”
Section: Chemically Regulated Nuclear Import Of Gr-cop1 Coimports Uvr8mentioning
confidence: 99%
“…However, it should be noted that chromatin association of UVR8 has recently been challenged (39). Independent of this controversy, the GFP-UVR8…”
Section: Chemically Regulated Nuclear Import Of Gr-cop1 Coimports Uvr8mentioning
confidence: 99%
“…The significance of the association of UVR8 with chromatin remains an enigma; it is not clear whether the detection by ChIP of UVR8 at some loci it regulates (Brown et al 2005; Cloix and Jenkins 2008) indicates a functional necessity for the recruitment and/or activation of chromatin modifiers and/or transcription factors, which would underpin transcriptional regulation, or whether the association is simply due to non-specific chromatin binding because of an affinity for histones (Brown et al 2005; Cloix and Jenkins 2008). UVR8’s association with chromatin is certainly much weaker than that of transcription factors such as HY5, raising questions regarding its significance (Binkert et al 2016). The main objectives of this study were to test whether UVR8 influenced transcription through chromatin modification and to investigate whether it interacted directly with several known chromatin modifiers.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, it is important to keep in mind that the association of UVR8 with chromatin might be non-specific, resulting from UVR8’s ability to stick to histones during chromatin isolation. Binkert et al (2016) recently questioned the in vivo UVR8-chromatin association after failing to detect UVR8 on certain loci, including HY5 .…”
Section: Introductionmentioning
confidence: 99%
“…Although HY5 plays critical roles in UVB signaling, it lacks a transcriptional activation domain and cannot alone activate transcription Stracke et al, 2010). In addition, UVR8 does not seem to interact directly with HY5 (Heijde et al, 2013;Binkert et al, 2016). Binkert et al (2016) suggested that there may be HY5 partner protein(s) that provide a transcriptional activation domain and enable UVB responsive gene expression.…”
Section: Role Of Sh1 In Lduvb-dependent Hypocotyl Elongation: a Modelmentioning
confidence: 99%
“…In addition, UVR8 does not seem to interact directly with HY5 (Heijde et al, 2013;Binkert et al, 2016). Binkert et al (2016) suggested that there may be HY5 partner protein(s) that provide a transcriptional activation domain and enable UVB responsive gene expression. In this study, significant differences in expression for CsHY5, but not for CsCOP1 and CsUVR8, were observed between UVB-sensitive and insensitive NILs.…”
Section: Role Of Sh1 In Lduvb-dependent Hypocotyl Elongation: a Modelmentioning
confidence: 99%